If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 = 3x Solving 23 = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 23 + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 23 + -3x = 0 Add '-23' to each side of the equation. 23 + -23 + -3x = 0 + -23 Combine like terms: 23 + -23 = 0 0 + -3x = 0 + -23 -3x = 0 + -23 Combine like terms: 0 + -23 = -23 -3x = -23 Divide each side by '-3'. x = 7.666666667 Simplifying x = 7.666666667
| -17=3x-8 | | -5x+46=5+9(8x-4) | | a^3-1698a-2704=0 | | -4x-10=11 | | 1m+10=80 | | 33-x=222 | | 3(9x+7)=27x-1 | | 5(3-2x)=10(4-2x)-85 | | 4(x-10)=5x-45 | | 2x-5x-2=-3+4x-43 | | y=-1+-0.1666666667x | | IV=ir | | a^4-1698a-2704=0 | | 88-6x=-10x+85 | | -46-8x=5(-7x+7) | | 3=5-2 | | 75+10=15h | | 2(1.5)-3y=2 | | 4u-6=-2 | | p-0.30p=25.20 | | -20=4w | | 8x+6x-20=60-6x | | 7x+4q=8+3q | | 2(y)+8=8 | | y=x^3-6x^2-36x+15 | | 8=0.25(-m-1) | | 3(-3+2x)=9 | | 3m+n=35 | | 3(x+1)+2(2x-6)=33 | | 3x^3+2x^2+-41x+-66=0 | | 8a-48=-6(-6-6a) | | 6(2-3x)=4(5x+7) |